Implementation of neurocritical care in Thailand - Viarasilpa, Tanuwong (Frontiers in Neurology, 2022)
Dedicated neurointensive care units and neurointensivists are rarely available in Thailand, a developing country, despite the high burden of life-threatening neurologic illness, including strokes, post-cardiac arrest brain injury, status epilepticus, and cerebral edema from various etiologies. Therefore, the implementation of neurocritical care is essential to improve patient outcomes. With the resource-limited circumstances, the integration of neurocritical care service by collaboration between intensivists, neurologists, neurosurgeons, and other multidisciplinary care teams into the current institutional practice to take care of critically-ill neurologic patients is more suitable than building a new neurointensive care unit since this approach can promptly be made without reorganization of the hospital system. Providing neurocritical care knowledge to internal medicine and neurology residents and critical care fellows and developing a research system will lead to sustainable quality improvement in patient care. This review article will describe our current situation and strategies to implement neurocritical care in Thailand.